Collaborative problem solving using public social network media: analyzing student interaction and its impact to learning process - (:unkn) unknown (The Society of Digital Information and Wireless Communications, 2015)
This paper examines the use of social network media at three aspects in African and Libyan perspective. Firstly, to use social network media as an open network learning environment that provide service for interaction necessary for learners to support socialization and collaboration during problem solving. Secondly, to use social media as a tool to support blended learning in e-learning system and encourage non-native English students to express their ideas and fill the gap of communication problems. Thirdly, to analyze the interaction of the learner in social media threaded messages and its relation to group and individual performance using different social schema and social network analyses. Quasi-experimental results indicate that there is an increase on the cognitive level of students at different level while qualitative results reveal that it helps deepen learning, memorable, have freedom to express opinions and lessen pressure and increase communication and socialization.
Article published in International Journal of Digital Information and Wireless Communications (IJDIWC)
This paper examines the use of social network media at three aspects in African and Libyan perspective. Firstly, to use social network media as an open network learning environment that provide service for interaction necessary for learners to support socialization and collaboration during problem solving. Secondly, to use social media as a tool to support blended learning in e-learning system and encourage non-native English students to express their ideas and fill the gap of communication problems. Thirdly, to analyze the interaction of the learner in social media threaded messages and its relation to group and individual performance using different social schema and social network analyses. Quasi-experimental results indicate that there is an increase on the cognitive level of students at different level while qualitative results reveal that it helps deepen learning, memorable, have freedom to express opinions and lessen pressure and increase communication and socialization.
Keywords: blended learning; collaboration; e-learning; network learning; socialization; social network media